2022
DOI: 10.1128/spectrum.01122-22
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Iminosugar Compounds Produced by Lactobacillus paragasseri MJM60645 and Their Anti-Biofilm Activity against Streptococcus mutans

Abstract: In this study, we isolated lactic acid bacteria that inhibit streptococcal biofilm from the oral cavity of infants and identified two novel compounds from the supernatant of their culture broth. The two compounds are structurally similar, and both consist of iminosugars, glycerol, and unsaturated fatty acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The underlying element might relate to the direct antagonistic activity of organic acid or the supportive action of acidic conditions to activate bacteriocin-like compounds that are active at low pH. 6,30,31,32 The ability of the bacterium CFS isolated from fermented foods to produce powerful antibiotic substances that can break the biofilm to battle S. mutans MTCC-890 colonization and biofilm formation was demonstrated. The cell wall production, cell metabolism, and cell attachments may all be impacted by the metabolites produced by the isolated probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying element might relate to the direct antagonistic activity of organic acid or the supportive action of acidic conditions to activate bacteriocin-like compounds that are active at low pH. 6,30,31,32 The ability of the bacterium CFS isolated from fermented foods to produce powerful antibiotic substances that can break the biofilm to battle S. mutans MTCC-890 colonization and biofilm formation was demonstrated. The cell wall production, cell metabolism, and cell attachments may all be impacted by the metabolites produced by the isolated probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Wasfi R et al [ 43 ] reported that biosurfactant produced by L. acidophilus can inhibit the biofilm formation of S. mutans . Gu, et al [ 44 ] discovered novel iminosugar compounds that can interfere with the biofilm formation of S. mutans . It is necessary to explore the active compound in further study.…”
Section: Discussionmentioning
confidence: 99%
“…The dry leaf of IXD was crushed and extracted with 70% ethanol at the ratio of 1.38% at 85 °C for 36 h. Then the filtrate was concentrated by using a rotary evaporator (EYELA, Japan) under vacuum. Lactobacillus strain MJM60645 was isolated from infant’s oral cavity as described in the previous study 26 . 16S rDNA sequence of MJM60645 showed 99% similarity with Lactobacillus paragasseri .…”
Section: Methodsmentioning
confidence: 99%